Gandhian Philosophy, Conflict Resolution Theory and Practical Approaches to Negotiation - THOMAS WEBER (Journal of Peace Research, vol. 38, no. 4, 2001, pp. 493-513, 2001)
It is puzzling that links between Gandhian social philosophy and recent conflict resolution/negotiation literature, especially given the latter's Gandhian `flavour', have received so little scholarly attention. While there seems to be no direct causal link between the two bodies of knowledge, conflict resolution literature in the guise of modern problem-solving and win-win (as opposed to power-based and zerosum) approaches leading to integrative conflict resolution (as opposed to mere compromise and distributive outcomes) strongly echoes Gandhi's own writings and the analyses of some Gandhi scholars. This is especially true in the case of non-mainstream writings that see conflict resolution techniques as potentially being about more than the solution of immediate problems, that see a broader personal and societal transformation as the ultimate goal. This article explores these connections and argues that Gandhian satyagraha should be squarely located within conflict resolution discourse.